CLASSROOM TECHNIQUES AND ACTIVITIES FOR READING (Ustozlar uchun, 2025)
In the modern educational process, reading plays a crucial role in developing students’ language competence. It helps learners expand vocabulary, improve comprehension, and enhance their ability to think critically. In teaching English as a foreign language, reading not only strengthens linguistic skills but also broadens cultural understanding. The purpose of this paper is to analyze effective classroom techniques and activities that enhance reading skills among students